AL-ASMA' FIL QUR'AN - M. Habiburrahman; Linda Suanti (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2025)
When discussing the Qur'an, it is essential to discuss all aspects related to it. Whether it is the way it is read or related to its language, namely Arabic. Understanding the messages conveyed by the Qur'an requires adequate knowledge, one of which is the Arabic language. One component of the Arabic language that we will discuss is al-Asma'. Al-Asma' is the plural form of al-ism, which is one of the three parts of a word in Arabic. Al-Asma' has an important position in Arabic sentence structure. In Arabic, al-asma' consists of 13 parts with various sub-parts, ranging from muzakkar, muannas, mamdud, maqsur, manqus, maswuf, alat, ism al-jins, isim al-'alam, dhamir, ism isyarah, ism mausul, ism istifham, ism ma'rifah, ism nakirah, and others. The rules of interpretation related to al-asma'. First, a noun that has multiple meanings, then its meaning is directed to the meaning contained in the context of the sentence. The second rule of asthma' is that if there are several contents standing alone in one text, then their meaning also includes other meanings contained therein. However, if it is related to a word (term) whose meaning is contained in that word (term), then its meaning does not include the accompanying word.